Caractérisation physique, chimique et microbiologique de trois sols acides tropicaux du Rwanda sous jachères naturelles et contraintes à leur productivité - Muhinda, Jean Jacques Mbonigaba; Nzeyimana, Innocent; Bucagu, Charles; Culot, Marc (Biotechnologie, agronomie, société et environnement, 2009)
Physical, chemical and microbiological characterization of three tropical acidic soils of Rwanda under natural fallows and productivity constraints. Three acidic soils of highland (HL), middle land (ML) and lowland (LL) from Rwanda were sampled respectively in the experimental stations of Gakuta, Tonga and Cyabayaga for a physical, chemical and microbiological characterization in order to determine their productivity constraints. Soils are strongly acidic in the HL and ML (pH 4.1 and 4.7) and moderately acidic in LL (pH 5.5). The rate of total organic carbon (C^sub org^) is acceptable in Gakuta (4.5%), but decreases with altitude. The total nitrogen (N^sub tot^), the phosphorus and the effective cation exchange capacity follow the same trend, their levels remaining nevertheless weak. Base saturation and Bray2-P content are weak in the HL and ML, but also they are negatively correlated with C^sub org^ content. The Al^sup 3+^ ion occupies 32 and 18% of the exchange complex at Gakuta and Tonga, and is non-existent in Cyabayaga soils. Carbon microbial biomass (C^sub mic^ : C^sub org^) and nitrogen microbial biomass (N^sub mic^ : N^sub tot^) ratios indicate a weak mineralization/immobilization rate in the highly acidic soils, and are positively correlated with soil pH. C^sub mic^ : N^sub mic^ ratio values obtained indicate a soil microbial population dominated by fungi, which predicts a poor organic matter (OM) quality. The small proportion of the assimilate carbon fraction at Gakuta (5% of C^sub org^) testifies also to the OM poor quality. Basal respiration rate is very low (0.30 - 0.37 µg CO^sup 2^.h^sup -1^.g^sup -1^). The addition of glucose for the substrate induced respiration has considerably stimulated the metabolic activity, which results in low values of respiratory activation quotient (Q^sub R^ = 0.4-0.5). Dehydrogenase and acidic phosphatase activities are very low but positively correlated with C^sub org^. The soil acidity remains the principal constraint to land productivity in the HL and ML regions while low soil OM and N contents would constitute a limitation in LL zone if appropriate land management practices are not used. [PUBLICATION ABSTRACT]